New data on Nothrotrombidium, Southcottella and Eatoniana larvae (Acari: Trombellidae, Neothrombiidae, Erythraeidae) from Iran - Javad Noei; Mohammad Mahdi Rabieh (Persian Journal of Acarology)
Larvae of Eatoniana lorestanicus (Saboori & Lachinani, 2003) (Acari: Erythraeidae) were collected ectoparasitic on Sphingonotus sp. (Orthoptera: Acrididae: Oedipodinae) in Chahkand village, Birjand city, South Khorasan province, Iran. New morphological data of E. lorestanicus is presented. Eatoniana lorestanicus, Southcottella nematii Saboori, 2002 and Nothrotrombidium birjandensis Noei, 2017 were recorded for the second time from Iran. Caradrina clavipalpis (Scopoli) (Lepidoptera: Noctuidae) and the genus Sphingonotus were recorded as host of Nothrotrombidium and Eatoniana larvae for the first time, respectively. A key to species of Eatoniana of the world (larvae) is provided.